Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/ijc.31804
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and commercial alcohols and esophageal cancer risk in Kenya

Abstract: Squamous cell esophageal cancer is common throughout East Africa, but its etiology is poorly understood. We investigated the contribution of alcohol consumption to esophageal cancer in Kenya, based on a hospital-based case-control study conducted from 08/2013 to 03/2018 in Eldoret, western Kenya. Cases had an endoscopy-confirmed esophageal tumor whose histology did not rule out squamous cell carcinoma. Age and gender frequency-matched controls were recruited from hospital visitors/patients without digestive di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 26 publications
(52 reference statements)
3
31
1
Order By: Relevance
“…Comparable distributions of religion and education between controls and KDHS data have been presented previously for our study population. 16 Geocoded residential locations of cases and controls occupied a comparable spatial extent-the median distance to MTRH was 54 km and 47 km, respectively.…”
Section: Participant and Exposure Characteristicsmentioning
confidence: 96%
“…Comparable distributions of religion and education between controls and KDHS data have been presented previously for our study population. 16 Geocoded residential locations of cases and controls occupied a comparable spatial extent-the median distance to MTRH was 54 km and 47 km, respectively.…”
Section: Participant and Exposure Characteristicsmentioning
confidence: 96%
“…Residential location of participants by (a) case and control status, (b) moderate/severe dental fluorosis status, in cases; (c) moderate/severe dental fluorosis status, in controls. 3 Other tooth brushing implement = 7 cases and 2 controls used hand/handkerchief. 4 DMFT = sum of decayed + missing + filled teeth (range 0 = best to 21 = worst in this sample).…”
Section: Principle Findingsmentioning
confidence: 99%
“…The hypothesized etiological model for this African EC corridor involves the presence of an unknown but highly spatially‐patterned factor conveying substantial risk, on top of which lifestyle factors act . In Kenya alcohol contributes to ESCC but to a lesser extent than in western countries . Among other potential contributors, poor oral health has not been examined comprehensively in Africa, but beyond the continent studies have found that different aspects of poor oral health status are associated with increased ESCC risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report on fieldwork experience in the pilot phase of an esophageal squamous cell carcinoma casecontrol study in Western Kenya. The study proceeded to the main study which has now recruited over 400 cases and 400 controls (cumulative) and its first results are emerging 10 . The pilot study called for protocol changes and considerations specific to this setting, which are discussed below and from which we make recommendations for fieldwork (R1-R9) in Box 1.…”
Section: Discussionmentioning
confidence: 99%